Endothelial-Dependent Fibrinolysis in Subjects with the Lupus Anticoagulant and Thrombosis - Francis, Robert B, Jr.; McGehee, William G; Feinstein, Donald I (Thrombosis and Haemostasis, 1988)
To investigate the hypothesis that diminished endothelial fibrinolytic activity contributes to the pathogenesis of thrombosis in patients with the lupus anticoagulant (LA), we assessed the ability of endothelium to release tissue-type plasminogen activator (t-PA) in response to standardized venous occlusion (VO) of the arm, and the extent of inhibition of t-PA, in 11 subjects with LA and a history of thrombosis and in 36 healthy normal subjects. The mean rise in plasma t-PA antigen after VO, the mean plasma free t-PA activity after VO, and the mean plasma t-PA inhibitor level prior to VO were not significantly different in subjects with LA and thrombosis and in normal subjects. Four subjects with LA and thrombosis (36%), and five of 36 healthy control subjects (14%) generated no detectable free t-PA activity after VO (“non-responders”); this difference was not statistically significant. All four “non-responders” with LA and thrombosis had normal t-PA antigen release after VO, indicating that the lack of detectable free t-PA activity after VO was due to increased inhibition of released t-PA. We conclude that abnormally reduced endothelial fibrinolytic activity is not present in the majority of subjects with LA and thrombosis. In the subset of subjects with LA and thrombosis who generate no detectable t-PA activity after VO, a stimulatory effect of LA on endothelial production of t-PA inhibitor cannot be excluded.
Keywords: Fibrinoly; Thrombosis; Lupus anticoagulant; Endothelium